Analisa Usaha Pengolahan Rajungan (Portunus Pelagicus) Pada Masa Pandemi Covid 19 - Handri Jurya Parmi; Junaidi Junaidi; Ria Ashari (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
This study aims to determine the feasibility of the ranjungan crab processing business in the hamlet of Pemongkong village, East Lombok district during the covid 19 pandemic. The research method used is a descriptive method with a survey approach. Data collection methods in this study were observation, interviews and questionnaires. The types and sources of data in this study are primary and secondary data. The analytical method used is business analysis with income analysis. The results showed that the ranjungan crab processing business was feasible even though during the covid 19 pandemic in the hamlet of the Pemongkong village, East Lombok district, this can be seen from the total income received which was much greater than the total costs incurred. The ranjungan crab (Portunus pelagicus) processing business is very promising and deserves to be developed